A Green Criminology Perspective on the DPA Mechanism: Corporate Impurity in Environmental Crimes Post the Job Creation La - Arif Rahman Hakim; Evi Retno Wulan (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Environmental protection in Indonesia faces increasingly serious structural challenges following the enactment of the Criminal Procedure Law Number 20 of 2025 (the Criminal Code / KUHP), which for the first time introduces the Deferred Prosecution Agreement (DPA) mechanism for corporations. This study aims to: (1) analyze the normative framework of the DPA mechanism under Article 328 of the 2025 Criminal Code and assess its alignment with the principle of primum remedium as well as the constitutional right to a clean and healthy environment as guaranteed by Article 28H of the 1945 Constitution; (2) identify normative conflicts between the 2025 Criminal Code, Law Number 32 of 2009 on Environmental Protection and Management (UUPPLH), Law Number 1 of 2023, and Law Number 6 of 2023 concerning Job Creation; and (3) formulate minimum normative standards to ensure that criminal proceedings in environmental crimes are constitutional and in line with the principles of ecological justice. This study employs a normative legal research method through a statutory approach and a conceptual approach grounded in a green criminology perspective. The findings indicate that the simultaneous interaction among the Job Creation Law, the 2023 Criminal Code, and the 2025 Criminal Code collectively constructs a three-layered